Pancreas Divisum in Pediatric Acute Recurrent and Chronic Pancreatitis: Report From INSPPIRE. Issue 6 (July 2019) - Lin, Tom K.; Abu-El-Haija, Maisam; Nathan, Jaimie D.; Palermo, Joseph P.; Barth, Bradley; Bellin, Melena; Fishman, Douglas S.; Freedman, Steven D.; Gariepy, Cheryl E.; Giefer, Matthew J.; Gonska, Tanja; Heyman, Melvin B.; et al.
Abstract : Introduction: The significance of pancreas divisum (PD) as a risk factor for pancreatitis is controversial. We analyzed the characteristics of children with PD associated with acute recurrent or chronic pancreatitis to better understand its impact. Patients and Methods: We compared children with or without PD in the well-phenotyped INSPPIRE (INternational Study group of Pediatric Pancreatitis: In search for a cuRE) cohort. Differences were analyzed using 2-sample t test or Wilcoxon rank sum test for continuous variables, Pearson χ 2 or Fisher exact test for categorical variables. Results: PD was found in 52 of 359 (14.5%) subjects, a higher prevalence than the general population (∼7%). Females more commonly had PD (71% vs. 55%; P =0.02). Children with PD did not have a higher incidence of mutations in SPINK1, CFTR, CTRC compared with children with no PD. Children with PD were less likely to have PRSS1 mutations (10% vs. 34%; P <0.01) or a family history of pancreatitis ( P <0.05), and more likely to have hypertriglyceridemia (11% vs. 3%; P =0.03). Children with PD underwent significantly more endoscopic procedures and pancreatic sphincterotomy. Patients with PD had fewer attacks of acute pancreatitis ( P =0.03) and were less likely to develop exocrine pancreatic insufficiency ( P =0.01). Therapeutic endoscopic retrograde cholangiopancreatography was considered most helpful if pancreatic duct was impacted with stones (83% helpful). Conclusions: PD is likely a risk factor for acute recurrent pancreatitis and chronic pancreatitis in children that appears to act independently of genetic risk factors. Patients with PD and stones obstructing the pancreatic duct benefit most from therapeutic endoscopic retrograde cholangiopancreatography.